PENGARUH ARUS KAS DAN LABA BERSIH TERHADAP TINGKAT PENGEMBALIAN SAHAM PADA PERUSAHAAN PENGHASIL BAHAN BAKU SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Panji Pramuditha; Mirza Fazlur Rahman (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
This research was conducted to determine the influence of cash flow and net income to stock return on the agriculture companies listed at the Indonesia Stock Exchange in periode 2009-2013 either partially or simultaneously. The method used in this research is descriptive and verificative. The sample used in this study is the annual financial statements 6 agriculture companies listed at the Indonesia Stock Exchange 2009-2013. To determine the effect of cash flow and net income to stock return multiple regression analysis. The results of this research indicate that in partial cash flow have a significant influence to stock return. The same thing happened to net income have a significant influence to stock return. At the same time this research showed that simultaneous cash flow and net income provide a significant effect to stock returns. The rest can be explained by other variables not examined. Keywords : Cash Flow, Net Income, Stock Return.